Rehabilitation of Red Mud Pond - a Pilot Study at Indal, Belgaum (Karnataka) - Chauhan, Suresh; Sharma, Jitendra Vir; Lal, Banwari; Paul, Varghese (Indian Forester, 2006)
Based on the findings of the research trials on the rehabilitation of red mud conducted by TERI, New Delhi, a field experiment was implemented on pilot basis over 1.08 ha of the red mud pond at INDAL, Belgaum, Karnataka. Optimum combination, identified in the trials i.e., Red mud + 25% FYM + 15% Gypsum + 5% Vegetative dry dust + Bacteria + Mycrorrihaza, was used for the field experiment. Five tree species, i.e., Prosopis juliflora, Pongamia pinnata, Acacia nilotica, Leucaena Leucocephala and Albizia lebbek and five grass/legumes species i.e., Brachiaria mutica, Chloris gayana, Sesbania sesban, Brachiaria decumbens and Stylosanthes scabra, identified through the research trials, were grown in the experimental plot. The findings reveal remarkable changes in physical and chemical characteristics of red mud after amendment, which provides conducive medium for plants to grow. After thirteen months, among the tree species, Leuacaena leucocephala species showed maximum average growth rate and low mortality, while among the grass/legumes, all the five species gave good growth and survival. The micronutrients contents increased and alkalinity of the red mud decreased up to seven months from the start of the experiment. However, after seven months there was reduction in the micronutrients contents and increase in the alkalinity of the red mud, which is due to the uptake of micronutrients by the plants.